2013
DOI: 10.1111/tbed.12050
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Schmallenberg Virus and Seroprevalence in Belgian Sheep and Goats

Abstract: SummaryA serological survey to detect Schmallenberg virus (SBV)-specific antibodies by ELISA was organized in the Belgian sheep population to study the seroprevalence at the end of the epidemic. One thousand eighty-two sheep samples which were collected from 83 herds all over Belgium between November 2011 and April 2012 were tested. The overall within-herd seroprevalence and the intraclass correlation coefficient were estimated at 84.31% (95% CI: 84.19-84.43) and 0.34, respectively. The overall between-herd se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 14 publications
8
40
2
2
Order By: Relevance
“…Herd seroprevalence in this study (53.3%) was alarming and somehow expected after the several outbreaks and sever economic losses from SBV detected from 2011 till now in many European and Mediterranean countries like Germany, France, Belgium, Italy, Spain, Greece, turkey and others. Interestingly, our results were lower to what was previously shown in Belgium for example (above 80% of the herds) (Méroc et al, 2013) and higher than Turkey (39.8%) (Azkur et al, 2013). This study present for the first time, a clear evidence that SBV and Simbu group viruses are already spread in Lebanon and that most of the Lebanese flocks had been in contact with SBV or other Simbu group viruses somehow.…”
Section: Fig 1 Prevalence Of Sbv/simbu Group Viruses Herds In the Dcontrasting
confidence: 88%
“…Herd seroprevalence in this study (53.3%) was alarming and somehow expected after the several outbreaks and sever economic losses from SBV detected from 2011 till now in many European and Mediterranean countries like Germany, France, Belgium, Italy, Spain, Greece, turkey and others. Interestingly, our results were lower to what was previously shown in Belgium for example (above 80% of the herds) (Méroc et al, 2013) and higher than Turkey (39.8%) (Azkur et al, 2013). This study present for the first time, a clear evidence that SBV and Simbu group viruses are already spread in Lebanon and that most of the Lebanese flocks had been in contact with SBV or other Simbu group viruses somehow.…”
Section: Fig 1 Prevalence Of Sbv/simbu Group Viruses Herds In the Dcontrasting
confidence: 88%
“…Yalnızca artropodlarla veya transplasental olarak nakledilebilen SBV'nin, geçişinin cinsiyete ve yaşa bağlı-lık göstermediği daha önceki çalışmalarda bildirilmiştir (16,20,24). Sunulan çalışmada; SBV'nin seroprevalansı ile cinsiyet ve yaş grupları arasındaki ilişki istatistiksel olarak değerlendirilmemiş, ancak seropozitifliğe hem koyunda hem koçta, ≥2-<4 ve ≥4-<6 yaş gruplarında rastlanmıştır.…”
Section: Tartışma Ve Sonuçunclassified
“…nakledildiği tespit edilirken, ruminantların enfeksiyona duyarlı oldukları gözlenmiştir (6,13,22,26). Schmallenberg virüs; Hollanda, Almanya, Belçika, Fransa, İtalya, Büyük Britanya, Lüksemburg ve İspanya'da malforme kuzu, oğlak ve buzağıların beyninde belirlenirken (4), transplasental geçişin de olduğu ortaya konulmuştur (16,26). Ruminantlara ek olarak köpeklerde de SBV'ye rastlanmıştır (21,25).…”
Section: Introductionunclassified
“…In a retrospective study in Turkey, employing indirect ELISA to screen 1362 serum samples collected from slaughterhouse animals between 2006 and 2013, the overall seroprevalence for SBV infection was found to be 24.5%, comprising 39.8% cattle, 1.6% sheep, 2.8% goats and 1.5% Anatolian water buffaloes, which indicated that the exposure of domestic ruminants to SBV in Turkey may have occurred up to five years prior to the first recorded outbreak of the disease in 2011 (Azkur et al 2013). In Belgium, a serological survey of 1082 sheep and 142 goats to detect SBV-specific antibodies by ELISA revealed a 98.03% overall between-herd seroprevalence in sheep and a 40.68% within-herd seroprevalence in goats (Meroc et al 2013b). So far, infections with SBV have been detected in Germany, the Netherlands, Belgium, the United Kingdom, France, Italy, Luxembourg, Spain, Denmark, Estonia, Switzerland, Ireland, Northern Ireland, Norway, Sweden, Finland, Poland, Austria, Switzerland and Turkey (Elbers et al 2012;Azkur et al 2013;FLI 2013a;Larska et al 2013;Meroc et al 2013a,b;Sailleau et al 2013).…”
Section: History and Geographic Distributionmentioning
confidence: 99%